EFFICIENT AND SUSTAINABLE ENERGY MANAGEMENT FOR HOSPITAL BUILDING - Sakinah Annura; Jihan Arabikum; Rahmawati Aminingrum; Zainal Ulu; Dwi Wahyudi; Lilik Zuhriyah (Universitas Brawijaya, 2022)
The development of current environmental problems raises the concerns of investors or hospital lenders about the potential financial problems resulting from current environmental problems. A sustainable health care system can achieve high-quality care and improve public health without wasting resources. The health service sector is continuously encouraged to apply the concept of